Transport properties of moisture and ionic chelators in concrete - Lu, Rongwei; Guan, Xinchun (Frontiers in Materials, 2023)
The laws of water and ionic chelator transport within concrete were experimentally investigated. It was found that the smaller the radius of the capillary pore within the concrete, the longer it takes to saturate it with water. The different pore sizes of capillaries take different times to reach saturation, which is one of the reasons for the "square root shift phenomenon" of capillary water absorption in concrete. The effect of initial concentration, different ions, transport media, wet and dry cycles and other factors on the transport process of ionic chelators within concrete was investigated by ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometer). It shows that the higher the initial concentration, the easier it is for the ion chelators to be transported inside the concrete within a certain transport depth range. However, after a certain range of transport depth, the initial concentration does not have a significant effect on the transport of the ion chelators. This is not the same as the transport pattern of non-chelated ions. Comparing the transport processes of chelated and non-chelated ions within the concrete, it was found that chelated ions form aggregation zones when transported within the concrete. The analysis suggests that the repair of pores and cracks within the concrete by the chelating agent promotes the creation of aggregation zones. Other factors such as the presence of chelated ions, the transport medium, changes in porosity, and wet and dry cycles can all influence the formation of chelated ion aggregates.